Perbandingan Waktu Pemecahan Password Menggunakan Algoritma Hash MD5, SHA-256, dan SHA-512 pada Serangan Brute Force - Nur Bainatun Nisa; Noni Fauzia Rahmadani; Aulia Kartika Dewi; Luftia Rahma Nasution; Dzilhulaifa Siregara; Rifdah Syahputri; Ibnu Rusydi (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2026)
Password security is a critical component in protecting information systems, as passwords are often the primary target of various attacks, particularly brute force attacks. A brute force attack works by systematically attempting all possible character combinations until the correct password corresponding to a stored hash value is found. Therefore, the choice of an appropriate hash algorithm plays a significant role in determining a system’s resistance to such attacks. This study aims to analyze and compare the password cracking time of MD5, SHA-256, and SHA-512 hash algorithms under brute force attack scenarios. The research methodology involves generating hash values from a set of test passwords using each hash algorithm, followed by conducting brute force attacks to recover the original passwords based on the generated hash values. The collected data are analyzed by measuring the time required to crack passwords for each algorithm. The results indicate that MD5 has the fastest cracking time compared to SHA-256 and SHA-512, indicating a lower level of resistance to brute force attacks. SHA-256 demonstrates better security than MD5 but remains less resistant when compared to SHA-512. The SHA-512 algorithm requires the longest cracking time, reflecting the highest level of resistance to brute force attacks among the tested algorithms. In conclusion, hash algorithms with larger bit lengths provide stronger protection against brute force attacks and are more suitable for secure password storage in information systems.